Dowry and Panaik Money from an Islamic View (Case Study of Makassar Bugis Community Marriages in Asmat Regency, South Papua) - Ayu Pramudia Kusuma Wardani; Khuriyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study aims to explain the views of Islamic law on dowry in marriages of the Bugis Makasar community in Asmat Regency, South Papua, the views of Islamic law on Money panaik in marriages of the Bugis Makasar community in Asmat Regency, South Papua, and the views of the Bugis Makasar community on the implementation of dowry and Money panaik in marriage. Within the Makasar Bugis ethnic group, several cultural groups and ancestral traditions are still practiced today. Including those carried out at wedding ceremonies. Before someone can get married, it is mandatory in Bugis society to give “Uang Panai” to the woman's family. In Bugis society, it is as if the bride's money determines whether a marriage will take place, and if it is not fulfilled then the marriage can be postponed or cancelled. Even though in the Islamic perspective it mandates the concept of